2015
DOI: 10.6018/analesps.31.2.169711
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between attachment styles and internalizing or externalizing symptoms in clinical and nonclinical adolescents

Abstract: Título: Relación entre los estilos de apego y los síntomas externalizantes e internalizantes en adolescentes clínicos y no clínicos. Resumen: Los estudios sobre la relación entre apego y psicopatología durante la adolescencia, se han realizado separadamente en muestras clínicas y no clínicas de adolescentes y han utilizado instrumentos de evaluación diferentes, lo que en conjunto ha podido dar lugar a un sesgo metodológico que ha incrementado la asociación entre apego y psicopatología. Con objeto de evitar est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
22
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 41 publications
8
22
2
2
Order By: Relevance
“…This would be consistent with Muris et al's (2003) suggestion that avoidantly attached youth may be disposed to ex -1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 ternalizing problems because they adopt strategies to minimize their distress such as being hostile and defensive towards others in order to avoid close attachment relationships. These results are also consistent with prior research that has found significant associations of avoidant attachment with externalizing behaviors (Ramos et al, 2016;Nishikawa et al, 2010), although other studies have not found such an association (Brumariu & Kerns, 2010;Lacasa et al, 2015). Thus, further research is likely needed into the associations between attachment avoidance and externalizing symptoms.…”
Section: Attachment Avoidance Personality Vulnerability and Psychopsupporting
confidence: 91%
See 2 more Smart Citations
“…This would be consistent with Muris et al's (2003) suggestion that avoidantly attached youth may be disposed to ex -1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 ternalizing problems because they adopt strategies to minimize their distress such as being hostile and defensive towards others in order to avoid close attachment relationships. These results are also consistent with prior research that has found significant associations of avoidant attachment with externalizing behaviors (Ramos et al, 2016;Nishikawa et al, 2010), although other studies have not found such an association (Brumariu & Kerns, 2010;Lacasa et al, 2015). Thus, further research is likely needed into the associations between attachment avoidance and externalizing symptoms.…”
Section: Attachment Avoidance Personality Vulnerability and Psychopsupporting
confidence: 91%
“…Furthermore, gender might also be a factor in the development of attachment styles and psychopathology. For example, in both clinical and non-clinical samples, female gender has been associated with an anxious attachment style, and male gender has been associated with an avoidant attachment style during adolescence (see Lacasa, Mitjavila, Ochoa, & Balluerka, 2015). Moreover, in the large majority of studies (e.g.…”
Section: Attachment Theory and Internalizing And Externalizing Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge is that, despite the potential for family services to address disparities in outcomes for vulnerable families, they remain underutilised in practice because they fail to address not only the economic but also the cultural obstacles to families' access and use of services (Kumpfer, Magalhães and Xie, 2017 [95]). The challenge is then to identify good practices and effective initiatives for the "hard-to-reach" families.…”
mentioning
confidence: 99%
“… 1 In terms of convergent validity, Roskam et al ( 2011 ) found a relationship between secure attachment as evaluated using the CA-MIR in both mothers and fathers and secure attachment in children referred for externalizing behavior problems at 4 years, as assessed using the French version of Attachment Q-Sort (Pierrehumbert et al, 1995a , b ). The instrument also showed discriminant validity with respect to measures of a range of psychopathological constructs in studies with clinical samples: psychotic patients (Benony et al, 2001 ), adolescents with eating disorders and substance abuse (Pierrehumbert et al, 2002 ; Miljkovitch et al, 2005 ), and groups with a range of different disorders (Lacasa et al, 2015 ). …”
mentioning
confidence: 99%